Electrochemical behavior of heat treated AL 2014 alloy using Azithromycin compound in 3.5% NaCl solution. (2022) - Nataraja, G.; Praveen, B.M.; Pruthviraj, R.D.; kempahanumakkagari, Sureshkumar; Ramakrishnappa, T.
Abstract: In the present research work, corrosion behavior of heat treated Al 2014 alloy in 3.5% NaCl with and without heat treatment in different concentration of inhibitors is studied. Rectangular specimen 2 cm X 1 cm X 1 mm was subjected heat treatment for 2 h, 4 h and 6 h in Muffle furnace at 550 °C. The specimen were tested for corrosion characterization of Electrochemical studies test. The result obtained is compared with heat treated and non-heat treated specimen. It was found that the heat treated specimen exhibits excellent corrosion Resistance when compared to non-heated specimen.